An innovative hematopoietic stem cell gene therapy approach benefits CLN1 disease in the mouse model. Issue 4 (6th March 2023) - Peviani, Marco; Das, Sabyasachi; Patel, Janki; Jno‐Charles, Odella; Kumar, Rajesh; Zguro, Ana; Mathews, Tyler D; Cabras, Paolo; Milazzo, Rita; Cavalca, Eleonora; Poletti, Valentina; Biffi, Alessandra
Abstract: Hematopoietic stem and progenitor cells (HSPCs) can establish a long‐lasting microglia‐like progeny in the central nervous system of properly myeloablated hosts. We exploited this approach to treat the severe CLN1 neurodegenerative disorder, which is the most aggressive form of neuronal ceroid lipofuscinoses due to palmitoyl‐protein thioesterase‐1 (PPT1) deficiency. We here provide the first evidence that (i) transplantation of wild‐type HSPCs exerts partial but long‐lasting mitigation of CLN1 symptoms; (ii) transplantation of HSPCs over‐expressing hPPT1 by lentiviral gene transfer enhances the therapeutic benefit of HSPCs transplant, with first demonstration of such a dose–effect benefit for a purely neurodegenerative condition like CLN1 disease; (iii) transplantation of hPPT1 over‐expressing HSPCs by a novel intracerebroventricular (ICV) approach is sufficient to transiently ameliorate CLN1‐symptoms in the absence of hematopoietic tissue engraftment of the transduced cells; and (iv) combinatorial transplantation of transduced HSPCs intravenously and ICV results in a robust therapeutic benefit, particularly on symptomatic animals. Overall, these findings provide first evidence of efficacy and feasibility of this novel approach to treat CLN1 disease and possibly other neurodegenerative conditions, paving the way for its future clinical application. Synopsis: CLN1 disease is caused by a deficiency of palmitoyl‐protein thioesterase 1 (PPT1). This is one of the most aggressive childhood neurodegenerative diseases with unmet medical needs. In this manuscript, we provide first evidence of the efficacy of a novel approach of hematopoietic stem cell (HSC)‐based gene therapy in the CLN1 mouse model. Transplantation of wild‐type HSCs attenuates the phenotype of Ppt1 −/− mice, reduces autofluorescent storage accumulation and neurodegeneration, and partially restores PPT1 enzymatic activity in the brain. Transplantation of PPT1 −/− HSCs transduced with a hPPT1‐encoding LV significantly increases survival and ameliorates the phenotype of Ppt1 −/− mice; this effect is enhanced when transduced HSCs are transplanted also in the central nervous system (CNS). HSC gene therapy prolongs survival and alleviates the phenotype of symptomatic Ppt1 −/− mice, especially when delivered also in the CNS. Transduced HSC transplantation is safe in Ppt1 −/− mice. Abstract : CLN1 disease is caused by a deficiency of palmitoyl‐protein thioesterase 1 (PPT1). This is one of the most aggressive childhood neurodegenerative diseases with unmet medical needs. In this manuscript, we provide first evidence of the efficacy of a novel approach of hematopoietic stem cell (HSC)‐based gene therapy in the CLN1 mouse model.